Joint Optimization Algorithm of Traffic Scheduling and Routing of Latency Sensitive Services for Time-Sensitive Networking - Wang, Yong; Yu, Kun; Shi, Jindou; Zhu, Xiaorong (2023 International Conference on Networks, Communications and Intelligent Computing (NCIC), 2023)
Time-Sensitive Networking (TSN) is considered to be an important means to achieve deterministic low-latency transmission, and traffic scheduling and routing are the keys to deterministic transmission. In this paper we first formulate the routing and scheduling joint optimization problem in TSN networks, where the schedulability of all data flows in the network is minimized by optimizing the transmission time slots of each data flow while considering routing. The optimal routing scheme is first determined using a heuristic algorithm, and then the scheduling scheme for each data stream is determined based on the constraints. To further optimize the schedulability ratio, the scheduling order among data flows is optimized using the Genetic Algorithm (GA). Simulation results show that compared with the traditional algorithms, the proposed algorithm has a higher schedulability and shorter running time even when the network size increases gradually.